The Potential Diagnostic Role of the Number of Ultrasonographic Characteristics for Patients with Thyroid Nodules Evaluated as Bethesda I–V - Sakashita, Tomohiro; Homma, Akihiro; Hatakeyama, Hiromitsu; Mizumachi, Takatsugu; Kano, Satoshi; Furusawa, Jun; Iizuka, Satoshi; Hoshino, Kimiko; Hatanaka, Kanako C.; Oba, Koji; Fukuda, Satoshi (Frontiers in Oncology, 2014)
Objective. Fine needle aspiration cytology (FNAC) is considered to be the most reliable method of examination for thyroid nodules. However, when thyroid nodules are evaluated as Bethesda I-V, the role of ultrasonography is considered to be enhanced. We investigated the association between a number of ultrasonographic (US) characteristics and the risk of thyroid malignancy, and assessed the optimal compromise on the number of US characteristics for predicting thyroid malignancy. Methods. Seventy-three patients, whose thyroid nodules were evaluated as Bethesda I-V by FNAC prior to surgery, were treated surgically. A number of US characteristics, such as microcalcification, irregular margins, hypoechogenecity, a taller-than-wide shape, and the absence of halo sign, were assessed before surgery. The optimal compromise on the number of US characteristics was analyzed using a receiver operating characteristics (ROC) curve. The area under the ROC curve (AUC) represents the overall discriminatory ability of a test. Results. The risk of malignancy was 11.8% in patients without any US characteristics, 44.4% in those with one characteristic, 61.5% in those with two characteristics, 75% in those with three characteristics, 90% in those with four characteristics, and 100% in those with five characteristics. The AUC was favorable (0.81599). At least two US characteristics were revealed to be the optimal compromise on the number of US characteristics based on the ROC curve. Conclusion. We proved the role of the number of US characteristics in predicting thyroid malignancy. It was thought that a surgical approach should be considered for patients with at least two US characteristics.